THIRD CENTURY ISLAMIC ECONOMIC THOUGHTS YAHYA BIN UMAR AND AHMAD BIN HANBAL III H / 9 M - Merison, Merison; Rahmi, Elvina; Nur, Ridho; Elfia, Elfia (State Institute of Islamic Studies (IAIN) Palu, 2020)
This article discusses the history of economic thought in the third century. Islam has provided all the guidelines or guidelines for humans to live in the world, both morally and economically. One of the most important economic activities that Islam promotes is the Qur'anic trade, and the hadith explains much about the profession. Where business is essential for the survival of humankind as civilization progresses on the surface of the earth, especially in the field of commerce where every trader competes for profit. Unfortunately, as the civilization of the traders begins to do everything to profit without regard to the rules laid down in the Shari'ah, One of the ways traders can benefit from unhealthy habits is to practice Siyasah al-Ighraq (dumping). And the people who talk about this are Yahya Bin Umar and Ahmad Bin Hanbal. The method in this study is library research aimed at studying the concept of a legal matter, using descriptive-analytical methods, normative-economic, and sociological approaches. The results show that the focus of Yahya bin Umar's attention is on the market rules that are reflected in the discussion of the bag (pricing). Implementation of prices (al-tas'ir) is a dominant theme in the book of Ahkam al-Suq, the author of the book, Imam Yahya bin Umar, repeatedly discussing it in various places. Apparently, he wants to say that price existence is an essential thing in a transaction and neglecting it can cause damage to people's lives. Related to this. Yahya bin Umar argues that al-tas'ir (pricing) cannot be done. Likewise, with Imam Ahmad, he criticized buyers who bought other people's goods at the same time. A seller who loses his price will monopolize the commodity, and if there is no competition, he can give it whatever he wants. Be more careful when making decisions. Imam Ahmad requested that such cases be remedied to avoid monopoly and other unpleasant practices.